Pengaruh Penerapan Biosekuriti Terhadap Produktivitas Usaha Peternakan Ayam Ras Petelur Di Kecamatan Kintamani, Kabupaten Bangli, Provinsi Bali - Wiwik Wahyuni; I Gusti Agus Maha Putra Sanjaya; Ni Ketut Etty Suwitari (Fakultas Pertanian, Universitas Warmadewa, 2021)
Biosecurity plays a major role in the productivity and continuity of the laying breed chicken farm. This study aims to determine the extent of the application of biosecurity and how the effect of the application of biosecurity on the business productivity of laying hens in Kintamani District, Bangli Regency, Bali Province. A structured questionnaire was used to obtain information from 25 respondents who were breeders of laying hens by interview and observation methods. This research was conducted from 10 August 2020 to 5 November 2020 in Kintamani District, Bangli Regency, Bali Province. The data were analyzed qualitatively and quantitatively using multiple linear regression analysis. The results showed that the level of application of biosecurity was at a very good level of application, namely 19 respondents (76%) and the level of good application was 6 respondents (24%) with those who had implemented the application of isolation and the application of very good sanitation, which amounted to the same amount as many 24 respondents (96%) while 18 respondents (72%) apply good livestock traffic control. From the research results also obtained the effect of the application of biosecurity is as follows: Y = 85.123 + 0.139X1 + 0.133X2 + 0.152X3 with R2 = 0.501. This shows that the application of Biosecurity has an effect of 50.1% on the Productivity of Laying Chicken Farms in Kintamani District, Bangli Regency, while the remaining 49.9% is explained by other factors not examined in this study.